The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge international handbooks, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Les pratiques traditionnelles affectant la santé physique et mentale des femmes; l'excision et l'infibulation - situation actuelle et perspectives d'avenir - Vissandjée, B.; Ndejuru, R.; Kantiébo, M.; Renaud, J.; Aïthachimi, L.; Levine, L.; Lapointe, M. (Institut universitaire SHERPA, 2001)
L’excision et l’infibulation sont parties intégrantes des traditions de nombreuses sociétés africaines issues majoritairement de la région subsaharienne. En contexte canadien, aucune information statistique n’est présentement disponible sur la prédominance de cette pratique, malgré le fait que de nombreux intervenants soupçonnent que plusieurs immigrant(e)s en provenance de ces pays sont susceptibles de faire subir ces pratiques à leurs fillettes. Cette étude qualitative explore les valeurs et les croyances des immigrant(e)s par rapport à ces pratiques traditionnelles, tout en cernant les défis de leur processus d’intégration au Canada et leur recours aux services de santé.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; care; corps; cours; discipline; interculturalité; migration; médecine; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences; sciences humaines; sciences infirmières; sex2283; sexologie; sexualité; thématiques; violences